2014
DOI: 10.1111/febs.12887
|View full text |Cite
|
Sign up to set email alerts
|

Akt enhances Runx2 protein stability by regulating Smurf2 function during osteoblast differentiation

Abstract: Runx2 plays essential roles in bone formation and chondrocyte maturation. Akt promotes osteoblast differentiation induced by the bone morphogenetic proteins BMP2 and enhances the function and transcriptional activity of Runx2. However, the precise molecular mechanism underlying the relationship between Runx2 and Akt is not well understood. In this study, we examined the role of Akt in regulating Runx2 function. We found that Akt increases the stability of Runx2 protein. However, the level of Runx2 mRNA was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 22 publications
3
65
0
Order By: Relevance
“…4). In addition, our data also provide a possible explanation for enhanced Runx2 activity via osteoanabolic agents including insulin and insulinlike growth factor-1, leading to activation of PI3K/Akt pathway that stabilizes Runx2 apparently by inactivating GSK3␤ by phosphorylating it at Ser 9 (26,42,43,47). Here, it is noteworthy to mention that although Wnt signaling is known to a play key role in maintaining bone mass where GSK3␤ and ␤-catenin are crucial signaling molecules, regulation of Runx2 by GSK3␤ in osteoblasts might be independent of Wnt signaling.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…4). In addition, our data also provide a possible explanation for enhanced Runx2 activity via osteoanabolic agents including insulin and insulinlike growth factor-1, leading to activation of PI3K/Akt pathway that stabilizes Runx2 apparently by inactivating GSK3␤ by phosphorylating it at Ser 9 (26,42,43,47). Here, it is noteworthy to mention that although Wnt signaling is known to a play key role in maintaining bone mass where GSK3␤ and ␤-catenin are crucial signaling molecules, regulation of Runx2 by GSK3␤ in osteoblasts might be independent of Wnt signaling.…”
Section: Discussionmentioning
confidence: 64%
“…5c, lower panel), suggesting that Fbw7 inhibition may restore Runx2 expression and its function. Increased Akt expression upon Fbw7 knockdown may apparently be attributed to stabilized Runx2, which is known to activate Akt (25,27,42,43). Like MC3T3-E1, Fbw7 RNAi in mouse primary calvarial osteoblasts showed similar results (Fig.…”
Section: Fbw7 Knockdown Restores Runx2 Expression and Enhancesmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, it has been reported that several E3 ubiquitin ligases promote Runx2 ubiquitination and degradation in osteoblasts, such as Smurf1, Smurf2, and WWP1. [40][41][42] We also checked whether AMPKα1 may regulate Runx2 via these E3 ubiquitin ligase. However, we did not find evidence of AMPKα1 regulating these E3 ubiquitin ligases or these E3 ubiquitin ligases regulating Runx2 in VSMC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena were evidently mitigated in the miR-29a transgenic mice. Post-translational modification of Runx2, a master osteogenic transcription factor, reportedly changes osteogenic reactions of osteoblast cultures [25]. We tested whether miR-29a modulation of HDAC4 affected the acetylation status of Runx2 in glucocorticoid-treated bone tissue.…”
Section: Accepted Manuscriptmentioning
confidence: 99%